2021
DOI: 10.1101/2021.04.20.440390
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decreased overall neuronal activity in a rodent model of impaired consciousness during absence seizures

Abstract: Absence seizures are characterized by a brief behavioural impairment including apparent loss of consciousness. Neuronal mechanisms determining the behavioural impairment of absence seizures remain unknown, and their elucidation might highlight therapeutic options for reducing seizure severity. However, recent studies have questioned the similarity of animal spike-wave-discharges (SWD) to human absence seizures both behaviourally and neuronally. Here, we report that Genetic Absence Epilepsy Rats from Strasbourg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…PO Connectivity and intrinsic cell dynamics are not homogeneous across PO, instead, there are distinct but overlapping input and output profiles (Casas-Torremocha et al, 2022, 2022; Guo et al, 2020) as well as highly varied burst patterns, that could explain the heterogeneity observed here (Desai and Varela, 2021). The complexity of thalamic neuronal dynamics at SWD onset extends to FO nuclei, where in VB neurons four groups of cells have been reported, including ‘onset peak’ and ‘sustained increase’ cells (McCafferty et al, 2021), similar to those reported here.…”
Section: Discussionsupporting
confidence: 83%
“…PO Connectivity and intrinsic cell dynamics are not homogeneous across PO, instead, there are distinct but overlapping input and output profiles (Casas-Torremocha et al, 2022, 2022; Guo et al, 2020) as well as highly varied burst patterns, that could explain the heterogeneity observed here (Desai and Varela, 2021). The complexity of thalamic neuronal dynamics at SWD onset extends to FO nuclei, where in VB neurons four groups of cells have been reported, including ‘onset peak’ and ‘sustained increase’ cells (McCafferty et al, 2021), similar to those reported here.…”
Section: Discussionsupporting
confidence: 83%